1992
DOI: 10.1213/00000539-199205000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Internal Jugular Vein Catheterization in Infants Undergoing Cardiovascular Surgery

Abstract: Central venous catheterization for pressure monitoring and drug administration is often important in the anesthetic management of infants undergoing cardiovascular surgery. We examined the effects of patient age, weight, and central venous pressure and the experience of the anesthesiologist on the rate of successful catheterization and catheterization time of the internal jugular vein (IJV) in a prospective study. We studied 106 infants undergoing IJV catheterization for cardiovascular surgery over a 7-mo peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
9

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 0 publications
2
46
0
9
Order By: Relevance
“…Mortensen et al (17) reported correlations between body weight and surface area with vein diameter, with a stronger correlation for femoral veins compared to internal jugular veins. Hayashi et al (18) conducted a cohort study assessing the use of US-guided CVC insertion in 106 children <20 kg and reported significantly lower success rates in infants <3 mo (81.3 vs. 100.0%, P < 0.05) and infants <4 kg (78.6 vs. 100.0%, P < 0.05) compared to children >3 mo and >4 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Mortensen et al (17) reported correlations between body weight and surface area with vein diameter, with a stronger correlation for femoral veins compared to internal jugular veins. Hayashi et al (18) conducted a cohort study assessing the use of US-guided CVC insertion in 106 children <20 kg and reported significantly lower success rates in infants <3 mo (81.3 vs. 100.0%, P < 0.05) and infants <4 kg (78.6 vs. 100.0%, P < 0.05) compared to children >3 mo and >4 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al (26) reported a success rate of 97.2% for percutaneous cannulations in 106 children; however, this success rate decreased to 81.3% when the patient was aged below three months.…”
Section: Discussionmentioning
confidence: 99%
“…65 A recent report examined the factors influencing successful cannulation of the internal jugular vein in infants using the high approach favoured by most institutions. 55 The overall success rate was 97.2% but this decreased to 78.6% with children < 4 kg.…”
Section: Internal Jugular Veinmentioning
confidence: 92%